2020
DOI: 10.1159/000511504
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte-Released Migrasomes in Urine Serve as an Indicator for Early Podocyte Injury

Abstract: <b><i>Background:</i></b> Levels of urinary microvesicles, which are increased during various kidney injuries, have diagnostic potential for renal diseases. However, the significance of urinary microvesicles as a renal disease indicator is dampened by the difficulty to ascertain their cell source. <b><i>Objectives:</i></b> The aim of this study was to demonstrate that podocytes can release migrasomes, a unique class of microvesicle with size ranging between 400 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(90 citation statements)
references
References 52 publications
2
88
0
Order By: Relevance
“…In 2018, another miRNome study of uEV from donors reported that the profile of miRNA did not discriminate between living donors and deceased donors before transplantation [ 62 ]. The role of miRNA in uEV after kidney transplantation is not yet fully explored as currently most diagnostic findings of miRNA are based on human kidney disease before transplantation [ 59 ], cultured kidney cell [ 30 , 63 ], animal model [ 63 , 64 ], or urine sample only with no uEV isolation or detection [ 57 , 65 , 66 , 67 , 68 ], rather than on uEV from KTR after transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, another miRNome study of uEV from donors reported that the profile of miRNA did not discriminate between living donors and deceased donors before transplantation [ 62 ]. The role of miRNA in uEV after kidney transplantation is not yet fully explored as currently most diagnostic findings of miRNA are based on human kidney disease before transplantation [ 59 ], cultured kidney cell [ 30 , 63 ], animal model [ 63 , 64 ], or urine sample only with no uEV isolation or detection [ 57 , 65 , 66 , 67 , 68 ], rather than on uEV from KTR after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some important findings or clues that are not included in Table 1 are introduced in this review to help highlight the directions for future studies. Kidney-specific markers are of great value in studying kidney allograft function and could reflect minimal changes, such as age-associated changes of the kidney in living donors [30][31][32]. Donor-specific markers could be identified by human leukocyte antigen (HLA) or specific gene sequences in nucleic acid cargos, according to differences in the genetic make-up between donor and recipient.…”
Section: Discussionmentioning
confidence: 99%
“…Gianesello et.al [18] proved that cubilin mediates albumin endocytosis in human podocytes, CUBN gene mutation may lead to the dysfunction of cubilin, thus affect albumin endocytosis. The development of proteinuria is usually related to podocyte damage, such as podocyte foot process effacement and cell loss [19]. Compared to megalin, cubilin is thought to have higher binding a nity for albumin [20].…”
Section: Discussionmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved More recently, Liu et al (2020) found that injured kidney podocytes generate more migrasomes than healthy podocytes. They proposed that urinary podocyte migrasomes could potentially be used as diagnostic markers for detecting early podocyte injury [13].…”
Section: Accepted Articlementioning
confidence: 99%
“…All rights reserved More recently, Liu et al (2020) found that injured kidney podocytes generate more migrasomes than healthy podocytes. They proposed that urinary podocyte migrasomes could potentially be used as diagnostic markers for detecting early podocyte injury [13]. Additionally, given the known physiological functions of migrasomes in cell-cell communication and in maintaining cellular homeostasis, we expect that in the future migrasomes will be implicated in diseases involving migrating cells such as tumour metastasis, immune disorders, developmental disorders and many others.…”
Section: Accepted Articlementioning
confidence: 99%